College of Physical Education and Sport Palestra Ltd.
Accredited College of Physical Education and Sport Palestra Ltd. is a private, non-universitary college which expands the list of education opportunities on the bachelor`s or master`s level with a focus on physical education and sport and leisure-time. College PALESTRA aims to be the leading Czech college raising high-quality experts in leisure-time and top-level sports, wellness, fitness development and activation of clients towards accepting healthy lifestyle. Outside the field of sport and health, we also aim to develop in the direction of pedagogy and sport management. College PALESTRA is going to continue providing top-quality education, the development of science and research activities, education of our own academic and scientific workers with a focus on motivating graduates to have a future academic career in conformity with societal demands and fulfilling the college social responsibility. College PALESTRA aims to cooperate more intensively with both domestic and foreign institutions of similiar focus in the field of research, exchange of knowledge, students and members of the academic staff. Even during long-term and stable raise in student and accredited study programme numbers, we aim to oreserve the friendly and forthcoming approach to the students. Part of the PALESTRA work is the Dual Career programme for Czech top athletes.